Psychological Distress and Life Satisfaction of Konkomba Widows in the Saboba District, Ghana - Nkyi, Anthony K; Djankpa, Gladys Barkei; Osae, Samuel (Journal of Advanced Psychology, 2021)
Purpose: The study sought to explore the influence of psychological distress and the life satisfaction among Konkomba widows who underwent widowhood rituals in the Saboba District in the Northern Region of Ghana. Specifically, the study sought to determine common widowhood rite practices that widows in the Saboba District undergo and to assess the level of life satisfaction among the Konkomba widows who have undergone widowhood rites in the Saboba district. Methodology: The purposive sampling technique stratified sampling technique, snowball sampling technique, and convenience sampling techniques were used to select one hundred and twenty (120) widows from the Saboba District. Data were analyzed using frequency distributions, means, standard deviations, regression analysis, and one-way analysis of variance (ANOVA). Results: Analyses of data revealed that generally, Konkomba widows in the Saboba District have significantly low satisfaction with life. Findings also disclosed that psychological distress had significantly negative relation with satisfaction with life of widows. Again, specific psychological distress predictors of satisfaction with life were Hostility, Paranoid Ideation, and Anxiety. Contribution to practice, theory and policy: The findings of the study will guide counsellors, clinical psychologists and health practitioners to formulate policies and treatment procedures aimed at helping widows to overcome the psychological consequences associated with bereavement and the practices of the outmoded widowhood rites. It is will also provide a framework for government institutions, NGOs, counsellors and health practitioners to incorporate a more comprehensive approach where the attention is given to widows' physical needs, psychological needs and social wellbeing.